2018
DOI: 10.15243/jdmlm.2018.053.1299
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of flora along Tourist Trails to Mt. Lamongan, East Java (Indonesia): Misconception of Restoration and Ecotourism Programs in Mountain Region?

Abstract: The aim of this research was to evaluate the diversity of plant species along the tourist trails to Mt. Lamongan and combat any misconceptions about ecosystem restoration and the ecotourism development program in Mt. Lamongan. A floristic survey was done through flora identification along the hiking trail from the gate of Mt. Lamongan nature recreation area in Papringan Village to the slopes of Mt. Lamongan. The identified species were listed and their taxonomic status analyzed using information from the GRIN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Hikers also use the 3–4 main trails to the mountain's summit, and the recreational park and waterfall at Ketenger on the lower slopes. Their presence may benefit the mountain's wildlife (Hakim et al, 2018), deterring trappers and providing income to local guides, many of whom nevertheless trap birds to supplement their income. However, Gunung Slamet is one of the main destinations for mountain hiking in Central Java, with thousands of people ascending the summit each year, and further regulation beyond ticketing may be required (Republika, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Hikers also use the 3–4 main trails to the mountain's summit, and the recreational park and waterfall at Ketenger on the lower slopes. Their presence may benefit the mountain's wildlife (Hakim et al, 2018), deterring trappers and providing income to local guides, many of whom nevertheless trap birds to supplement their income. However, Gunung Slamet is one of the main destinations for mountain hiking in Central Java, with thousands of people ascending the summit each year, and further regulation beyond ticketing may be required (Republika, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of restorative tourism on land have demonstrated how nature restoration and community driven initiatives can help to realize development goals by extending ecotourism into terrestrial regional and national parks and trails and poorer communities and regions (Campbell-Hunt 2014, Martinis et al 2015, Hakim et al 2018, Clark and Nyaupane 2022. Although marine restoration efforts are commonly more costly and marine ecosystems pose the added technological and logistical challenges of operating underwater (Bayraktarov et al 2016) and are affected by the "out of sight, out of mind" syndrome (Raffaelli et al 2005, Riera et al 2014, they promise to have similar effects and to bring restoration economies much closer to marine tourism hotspots.…”
Section: Restorative Tourismmentioning
confidence: 99%
“…In general, Adiantum grows in a moist and shaded environment (Awathi, 2009). This genus has members up to 250 species (Christenhusz, Zhang, & Schneider, 2011) and some of these species are found in Indonesia in various places with different altitudes (Hakim, Rahardi, & Rachmansyah, 2018;Lestari, Adjie, Jaruwatanaphan, Watano, & Pharmawati, 2014;Sukarsa, Apriliana, & Chasanah, 2011;Trimanto & Hapsari, 2016;Yusna, Sofiyanti, & Fitmawati, 2016). The basic chromosome number of Adiantum species range from 29 to 30 chromosomes (Christenhusz & Chase, 2014) and some of its members are polyploid organisms (F. H. Wang, Lu, Wen, Ebihara, & Li, 2016).…”
Section: Introductionmentioning
confidence: 99%